Efficient generation of brain organoids using magnetized gold nanoparticles - Hongwon Kim; Yoo-Jung Lee; Youngeun Kwon; Jongpil Kim (Scientific Reports, 2023)
Abstract Brain organoids, which are three-dimensional cell culture models, have the ability to mimic certain structural and functional aspects of the human brain. However, creating these organoids can be a complicated and difficult process due to various technological hurdles. This study presents a method for effectively generating cerebral organoids from human induced pluripotent stem cells (hiPSCs) using electromagnetic gold nanoparticles (AuNPs). By exposing mature cerebral organoids to magnetized AuNPs, we were able to cultivate them in less than 3 weeks. The initial differentiation and neural induction of the neurosphere occurred within the first week, followed by maturation, including regional patterning and the formation of complex networks, during the subsequent 2 weeks under the influence of magnetized AuNPs. Furthermore, we observed a significant enhancement in neurogenic maturation in the brain organoids, as evidenced by increased histone acetylation in the presence of electromagnetic AuNPs. Consequently, electromagnetic AuNPs offer a promising in vitro system for efficiently generating more advanced human brain organoids that closely resemble the complexity of the human brain.